Low-magnetism low-hydration-heat concrete and preparation method thereof

By using low-magnetic cement and demagnetized slag powder, combined with three-level gravel and air-induced water-reducing agent, the problems of hydration heat and magnetic instability of large-volume concrete in low magnetic environments are solved, and the effect of reducing magnetic properties and hydration heat is achieved, meeting the requirements of low magnetic environments.

CN119859045AInactive Publication Date: 2025-04-22CCCC FIRST HARBOR ENGINEERING CO LTD +2

Patent Information

Application Number
CN202510217635.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In marine engineering projects with low magnetic environment requirements, hydration heat and magnetic instability lead to magnetic exceeding standards, which cannot meet the requirements of low magnetic environment.

Method used

Low-magnetic cement and demagnetized slag powder are used as the cementitious material, and the combination of three-level gravel and air-induced water-reducing agents can reduce the hydration heat and magnetism of the concrete to ensure that the magnetic field strength is within the appropriate range.

Benefits of technology

It effectively reduces the magnetic properties and hydration heat of concrete, reduces the risk of cracking, meets the requirements of a low magnetic environment, and improves the reliability of engineering projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859045A_ABST
    Figure CN119859045A_ABST
Patent Text Reader

Abstract

The invention relates to the field of concrete, in particular to low-magnetism low-hydration-heat concrete and a preparation method thereof. The concrete comprises the following raw materials: a cementing material, fine aggregate, coarse aggregate, water and a water reducing agent, the cementing material comprises cement and slag powder, the cement accounts for 60%-70%, and the slag powder accounts for 30%-40%; the coarse aggregate adopts three-graded broken stone, the maximum particle size is 80 mm, the maximum value allowed by water transportation engineering specifications is met, and the use amount of a cementing material is effectively reduced and can be reduced by about 15% compared with that of common C30 concrete; the reduction of the cementing material not only can reduce the cost of the concrete and bring remarkable economic benefits, but also can reduce the hydration heat in the mass concrete, and does not need to add a hydration heat inhibitor to reduce the cracking risk of the concrete; the raw materials are detected by a metal detector, so that the raw materials are prevented from being mixed with magnetic substances, the slump of the concrete is 30-80mm, and the concrete is transported by adopting a hanging tank, a belt conveyor, a dumper and the like, so that the construction is convenient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete, and in particular to low-magnetic and low-hydration heat concrete and a preparation method thereof. Background Art

[0002] In current engineering construction, with the rapid development of magnetic fields such as magnetic detection and demagnetization technology in my country, the construction of geomagnetic observatories, magnetic detection laboratories and specific national defense projects has increased year by year. After completion of such projects, magnetic detection is usually required in a low-magnetic and stable and uniform environment to ensure the accuracy of the measurement. However, as the main building material in the project, the magnetism of concrete has become a key factor affecting the environmental magnetic field of these engineering projects.

[0003] For large-volume concrete structures in marine engineering projects, such as wave-breaking breast walls and precast blocks, the temperature rise caused by hydration heat may cause cracks, so controlling the core temperature of concrete within a reasonable range is one of the important contents in mix design. In marine engineering projects with high requirements for low magnetic environment, in addition to hydration heat control, the magnetism of concrete is also highly concerned. At present, the mix design of large-volume concrete mostly uses mineral admixtures to partially replace cement to reduce the generation of hydration heat. However, the magnetism of mineral admixtures is relatively unstable. When used in large-volume concrete, it is easy to cause the problem of excessive magnetism, which cannot meet the requirements of low magnetic environment. This magnetic instability has become a difficult problem affecting the quality of low magnetic engineering.

[0004] Therefore, in order to effectively control the hydration heat and magnetic level of concrete, the design of concrete mix with low magnetism and low cementitious material content has become a key research direction. If this technology can be realized, it will significantly improve the reliability of low-magnetic engineering projects and provide valuable technical experience for material selection and mix design of related construction projects. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a concrete and a preparation method thereof which can effectively reduce the magnetism of concrete and the hydration heat.

[0006] The present invention provides a low-magnetic and low-hydration heat concrete, comprising the following raw material components in parts by weight:

[0007] Cementitious material 280-300kg / m 3 , fine aggregate 690-730kg / m 3 , coarse aggregate 1230-1290kg / m 3 , water 134-140kg / m 3 , water reducing agent 2.8-3.0kg / m 3; The cementitious material includes cement and slag powder, wherein the cement accounts for 60%-70% and the slag powder accounts for 30%-40%;

[0008] The magnetic field strength of the cement is less than 5nT, and the magnetic field strength after magnetization by a 5mT magnetic field is less than 10nT;

[0009] The 7d activity index of the slag powder is ≥80%, the 28d activity index is ≥100%, and the loss on ignition is ≤1%; the magnetic field strength of the slag powder is <5nT, and the magnetic field strength after magnetization by a 5mT magnetic field is <10nT;

[0010] The magnetic field strength of the fine aggregate is less than 5nT, and the magnetic field strength after magnetization by a 5mT magnetic field is less than 10nT;

[0011] The magnetic field strength of the coarse aggregate is less than 5nT, and the magnetic field strength after magnetization by a 5mT magnetic field is less than 10nT;

[0012] The magnetic field strength of the concrete is less than 10nT, and the magnetic field strength after magnetization by a 5mT magnetic field is less than 15nT.

[0013] The low-magnetism and low-hydration heat concrete of this technical solution effectively reduces the magnetism and hydration heat of concrete, reduces the risk of concrete cracking, can meet the requirements of related special projects, and fills the gap in the low-magnetism large-volume concrete industry.

[0014] In some embodiments of the present application, the slag powder is blast furnace physical and chemical slag powder.

[0015] In some embodiments of the present application, the fine aggregate is machine-made sand, the matrix of the machine-made sand is limestone, and the stone powder content is ≤5%.

[0016] In some embodiments of the present application, the coarse aggregate is limestone crushed stone, and three levels are adopted, with particle size of 5-20 mm as the first level crushed stone, particle size of 20-40 mm as the second level crushed stone, and particle size of 40-80 mm as the third level crushed stone. The usage ratio of the first level crushed stone, the second level crushed stone, and the third level crushed stone is 2:5:3. The third level crushed stone with large particle size can effectively reduce the usage of cementitious materials, reduce the hydration heat of concrete, and reduce production costs.

[0017] In some embodiments of the present application, when antifreeze is required, an air-entraining water-reducing agent is used, and the water reduction rate of the air-entraining water-reducing agent is greater than 25%, so that the air content of the concrete is greater than 3%.

[0018] In some embodiments of the present application, the cement is ordinary No. 42.5 cement, wherein the components of clinker and gypsum are ≥ 86%, and the particle size of the cement is concentrated at 40±5 μm.

[0019] The present application also provides a method for preparing the above-mentioned low magnetic and low hydration heat concrete, which specifically comprises the following steps:

[0020] Demagnetization of raw materials: Demagnetize cement, slag powder and fine aggregate separately to meet the magnetic field strength requirements and then set aside;

[0021] Mixing: The coarse aggregate, demagnetized fine aggregate, demagnetized slag powder and demagnetized cement are sequentially passed through a belt conveyor equipped with a metal detector. When the metal detector sounds an alarm, the belt conveyor stops and removes the materials within the detection range of the metal detector. Then the belt conveyor sends the remaining materials detected by the metal detector into the mixer according to the proportion.

[0022] Stirring: The mixed materials are stirred for 15-30 seconds, and then water and a water reducing agent are added and stirred for 2-4 minutes to obtain the concrete.

[0023] In some embodiments of the present application, the cement and slag powder are screened using dry magnetic separation equipment to separate magnetic particles from non-magnetic slag powder particles. The magnetic particles are adsorbed in a magnetic field environment and guided to a separation device, while the non-magnetic slag powder particles continue to move along the conveying route for standby use.

[0024] The fine aggregate is treated by water washing so that the magnetic field strength of the fine aggregate meets the requirements.

[0025] In some embodiments of the present application, the slump of the concrete is 30 mm to 80 mm, and the concrete can be transported by hanging tanks, belt conveyors, dump trucks, etc., which facilitates construction.

[0026] In some embodiments of the present application, during the mixing process, the cylinder wall and blades of the mixer are made of 316L stainless steel to prevent the cylinder wall and blades from rusting and affecting the magnetism of concrete.

[0027] Based on the above technical solution, the low-magnetic and low-hydration heat concrete of the present invention solves the problem of unstable magnetic properties of traditional mineral powder and fly ash, effectively reduces the magnetism and hydration heat of concrete, reduces the risk of concrete cracking, can meet the requirements of relevant special projects, and fills the gap in the low-magnetic mass concrete industry;

[0028] The coarse aggregate uses three-grade crushed stone with a maximum particle size of 80mm, which meets the maximum value allowed by the water transport engineering specifications. At the same time, it can effectively reduce the amount of cementitious materials used, which can be reduced by about 15% compared with ordinary C30 concrete; the reduction of cementitious materials can not only reduce the cost of concrete and bring significant economic benefits, but also reduce the hydration heat in large-volume concrete, and there is no need to add hydration heat inhibitors to reduce the risk of concrete cracking; slag powder accounts for 30% to 40% of the concrete cementitious materials, which can further reduce the amount of cement, reduce the cost of concrete, and reduce hydration heat;

[0029] When preparing concrete, the raw materials are tested by metal detectors to avoid magnetic substances being mixed into the raw materials;

[0030] The slump of the concrete prepared by this scheme is 30mm to 80mm, and the concrete can be transported by hanging tanks, belt conveyors, dump trucks, etc., which is convenient for construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0032] Figure 1 is a graph showing the magnetization intensity of cement in Example 1 of the present invention;

[0033] Figure 2 This is a particle size distribution diagram of cement after demagnetization in Example 1 of the present invention;

[0034] Figure 3 This is a microscopic morphology of cement after demagnetization in Example 1 of the present invention;

[0035] Figure 4 This is a graph showing the magnetization intensity of the blast furnace physical and chemical slag powder in Example 1 of the present invention;

[0036] Figure 5 This is a particle size distribution diagram of the blast furnace physical and chemical slag powder after demagnetization in Example 1 of the present invention;

[0037] Figure 6 This is a microscopic morphology of the blast furnace physical and chemical slag powder after demagnetization in Example 1 of the present invention;

[0038] Figure 7 This is a temperature distribution profile diagram of the concrete block of Example 1 of the present invention 24 hours after pouring;

[0039] Figure 8 This is a temperature distribution profile diagram of the concrete block of Example 1 of the present invention 48 hours after pouring;

[0040] Fig. 9 This is a temperature distribution profile diagram of the concrete block of Example 1 of the present invention 72 hours after pouring;

[0041] Fig.10 This is a temperature distribution profile diagram of the concrete block of Example 1 of the present invention 96 hours after pouring;

[0042] Fig.11 This is a temperature distribution profile diagram of the concrete block of Example 1 of the present invention after 120 hours of pouring;

[0043] Fig.12 This is a simulation diagram of the block center temperature development trend of the concrete block according to the first embodiment of the present invention;

[0044] Fig.13 The photographs are before and after the freeze-thaw test of the concrete of the comparative example of the present invention;

[0045] Fig.14 These are photos of the concrete of Example 1 of the present invention before and after the freeze-thaw test. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Embodiment 1

[0048] This embodiment aims at preparing low-magnetic and low-hydration heat concrete for C30 mass concrete commonly used in marine engineering projects, including the following steps:

[0049] Demagnetization of raw materials:

[0050] Cement and blast furnace slag powder are screened using dry magnetic separation equipment. The dry magnetic separation equipment screens through magnetization, sorting and collection steps to separate magnetic particles from non-magnetic slag powder particles. The magnetic particles are adsorbed in the magnetic field environment and guided to the separation device, while the non-magnetic slag powder particles continue to move along the conveying route. In order to adapt to suspended powders of different particle sizes and densities, this embodiment also uses gravity sedimentation, gas sorting and other methods for auxiliary separation. By adjusting parameters such as magnetic field strength and dry magnetic separation equipment rotation speed, the adsorption effect of magnetic particles is adjusted to achieve the best separation effect.

[0051] After demagnetization, the magnetic field strength of cement was less than 5nT. After 5mT magnetization, the magnetic field strength of cement was less than 10nT. The saturation magnetization Ms of cement after demagnetization was 3.4~4.3×10 -4 emu / mg decreased to 1.7×10 -4 emu / mg, as attached Figure 1 As shown in the C1 curve, Figure 1 The C2 and C3 curves are the magnetization curves of untreated cement; the particle size distribution and micromorphology of demagnetized cement are as follows: Figure 2 and 3 As shown, the particle size of cement is concentrated at 40 ± 5 μm; then it is used;

[0052] The 7d activity index of the demagnetized blast furnace slag powder is ≥80%, the 28d activity index is ≥100%, and the ignition loss is ≤1%. The magnetic field strength test result is less than 5nT. After 5mT magnetization, the magnetic field strength of the blast furnace slag is tested again and is less than 10nT. The saturation magnetization Ms of the demagnetized blast furnace slag powder is 2.2~2.4×10 -4 emu / mg decreased to 1.6×10 - 4 emu / mg, can effectively remove magnetic substances that affect the magnetism of concrete, such as Figure 4 The G1 curve is shown in the figure. The G2 and G3 curves in the figure are the magnetization curves of the untreated blast furnace slag powder. The particle size distribution and microscopic morphology of the blast furnace slag powder after demagnetization are shown in Figure 5 and 6 As shown, the particle size of the mineral powder is concentrated at 25±5μm and is reserved;

[0053] The machine-made sand with stone powder content ≤5% and limestone as the parent rock is washed to meet the requirement that the magnetic field strength is less than 5nT. After 5mT magnetization, the residual magnetism change of the mineral powder is tested again to be less than 10nT;

[0054] mix:

[0055] In the order of particle size from large to small, limestone crushed stone, demagnetized machine-made sand, demagnetized blast furnace physical and chemical slag powder, and cement are sequentially passed through a belt conveyor equipped with a metal detector, wherein the cement is ordinary No. 42.5 cement, wherein the components of clinker and gypsum are ≥86%, and the median diameter of the cement is 15-18 μm; the 3d strength of the cement is ≥22 MPa, and the 28d strength is ≥46 MPa. When testing the magnetism of cement, a non-magnetic plastic box with a side length of 150 mm is filled with cement and placed in a magnetic shielding barrel. The magnetic detection probe is 5 cm away from the sample box. The magnetic detection result shows that the magnetic field strength is less than 5 nT. After 5 mT magnetization, the magnetic field strength of the cement is tested again and is less than 10 nT; the chemical composition of cement and slag powder is shown in Table 1;

[0056] Table 1 Chemical composition of cement and slag powder (%)

[0057]

[0058] The limestone crushed stones enter the belt conveyor in the order of the third-level crushed stones with a particle size of 40-80mm, the second-level crushed stones with a particle size of 20-40mm, and the first-level crushed stones with a particle size of 5-20mm. When the metal detector sounds an alarm, the belt conveyor stops, and the materials within the detection range of the metal detector are cleared or the magnetic abnormalities in the materials can be removed;

[0059] Then the belt conveyor will pass the metal detector to detect the remaining materials according to the limestone crushed stone 1283kg / m3 , machine-made sand after demagnetization 721kg / m 3 , Demagnetized blast furnace slag powder 116kg / m 3 、Cement 174kg / m 3 The limestone is sent into the mixer, where the magnetic field strength of the limestone is less than 5nT. After 5mT magnetization, the magnetic field strength is tested again and is less than 10nT. The limestone is used in the ratio of first-grade crushed stone, second-grade crushed stone, and third-grade crushed stone of 2:5:3, specifically, the third-grade crushed stone is 384.9kg / m 3 、Second level crushed stone 641.5kg / m 3 、First level crushed stone 256.6kg / m 3 ; By increasing the third-level crushed stone with large particle size, the amount of cementitious materials can be effectively reduced, the hydration heat of concrete can be reduced, and the production cost can be reduced;

[0060] Mixing: Mix the limestone gravel, machine-made sand, blast furnace slag powder and cement for 30 seconds, then add tap water 140kg / m 3 and polycarboxylate water reducer 2.8kg / m 3, Continue stirring for 2-4 minutes to obtain the concrete;

[0061] The slump of the obtained concrete is 30mm~80mm, and the concrete can be transported by hanging tanks, belt conveyors, dump trucks, etc., which is convenient for construction. The 7d strength of the concrete specimen under standard curing conditions is 32MPa~38MPa, and the 28d strength is 41MPa~46Mpa;

[0062] The concrete prepared as described above was used to make a cubic specimen with a side length of 150 mm. The magnetic field strength of the concrete specimen was 3.2 nT, and the magnetic field strength after magnetization with a 5 mT magnetic field was 7.9 nT.

[0063] The concrete obtained above was used to make a large-volume concrete block of 5m×4m×2.5m, and a hydration heat simulation analysis was performed. The formwork used a steel formwork to analyze the core temperature of the concrete block and the temperature difference between the inside and outside under the unfavorable conditions of a pouring temperature of 30℃ and an ambient temperature of 30℃. Figure 7-Figure 11 The temperature distribution cloud diagram is shown in Figure 24h, 48h, 72h, 96h and 120h after the concrete block is poured. It can be seen from the internal temperature field of the concrete block at the above five typical times that the highest temperature of the core of the concrete block occurs 96h after the pouring is completed, with the highest temperature being 66.0℃ and the maximum temperature difference between the inside and outside being 22.5℃, which meets the requirements of relevant specifications; the simulation diagram of the central temperature development trend obtained by numerical simulation is shown in Figure 2 Fig.12As shown; through the hydration heat calculation results, it can be seen that the concrete prepared with the above raw material mix ratio, even under unfavorable temperature conditions, the core maximum temperature and the temperature difference between the inside and outside also meet the requirements of the specification, and compared with ordinary concrete mix ratio, it can effectively reduce the risk of cracking.

[0064] Embodiment 2

[0065] Different from the first embodiment, in this embodiment, the raw material composition is: cement 168kg / m 3 , blast furnace slag powder 120kg / m 3 ; Limestone crushed stone: 1250kg / m 3 , specifically the third level crushed stone 375kg / m 3 、Second level crushed stone 625kg / m 3 、First level crushed stone 250kg / m 3 ; Machine-made sand 710kg / m 3 , tap water 138kg / m 3 , polycarboxylate water reducer 2.8kg / m 3 .

[0066] Embodiment 3

[0067] Different from the first embodiment, in this embodiment, the raw material composition is: cement 180kg / m 3 , blast furnace slag powder 110kg / m 3 ; Limestone crushed stone is 1290kg / m 3 , specifically the third level of crushed stone 387kg / m 3 、Second level crushed stone 645kg / m 3 、First level crushed stone 258kg / m 3 ; Machine-made sand 718kg / m 3 , tap water 138kg / m 3 , polycarboxylate water reducer 2.9kg / m 3 .

[0068] Embodiment 4

[0069] Different from the first embodiment, in this embodiment, the raw material composition is: cement 185kg / m 3 , blast furnace slag powder 115kg / m 3 ; Limestone crushed stone is 1265kg / m 3 , specifically the third level of crushed stone 380.4kg / m 3 、Second level crushed stone 632.5kg / m 3 、First level crushed stone 253kg / m 3 ; Machine-made sand 705kg / m 3 , tap water 137kg / m 3, polycarboxylate water reducer 2.9kg / m 3 .

[0070] Embodiment 5

[0071] Different from the first embodiment, in this embodiment, the raw material composition is: cement 175kg / m 3 , blast furnace slag powder 120kg / m 3 ; Limestone crushed stone: 1280kg / m 3 , specifically the third level crushed stone 384kg / m 3 、Second level crushed stone 640kg / m 3 、First level crushed stone 256kg / m 3 ; Machine-made sand 725kg / m 3 , tap water 134kg / m 3 , polycarboxylate water reducer 2.8kg / m 3 .

[0072] Embodiment 6

[0073] Different from the first embodiment, in this embodiment, the raw material composition is: cement 200kg / m 3 , Blast furnace slag powder 100kg / m 3 ; Limestone crushed stone: 1230kg / m 3 , specifically the third level crushed stone 369kg / m 3 、Second level crushed stone 615kg / m 3 、First level crushed stone 246kg / m 3 ; Machine-made sand 690kg / m 3 , tap water 134kg / m 3 , polycarboxylate water reducer 3.0kg / m 3 .

[0074] Embodiment 7

[0075] Different from the first embodiment, in this embodiment, the raw material composition is: cement 210kg / m 3 , blast furnace slag powder 90kg / m 3 ; Limestone crushed stone is 1240kg / m 3 , specifically the third level crushed stone 372kg / m 3 、Second level crushed stone 620kg / m 3 、First level crushed stone 248kg / m 3 ; Machine-made sand 708kg / m 3 , tap water 138kg / m 3 , polycarboxylate water reducer 2.9kg / m 3 .

[0076] Embodiment 8

[0077] Different from the first embodiment, in this embodiment, the raw material composition is: cement 195kg / m 3 , blast furnace slag powder 102kg / m 3 ; Limestone crushed stone is 1287kg / m 3 , specifically the third level crushed stone 386.1kg / m 3 、Second level crushed stone 643.5kg / m 3 、First level crushed stone 257.4kg / m 3 ; Machine-made sand 728kg / m 3 , tap water 137kg / m 3 , polycarboxylate water reducer 2.8kg / m 3 .

[0078] Comparative Example

[0079] Ordinary concrete components: cement 400kg / m 3 , crushed stone 954kg / m 3 , and the crushed stone particle size is 5-31.5mm, and the machine-made sand is 781kg / m 3 , water 165kg / m 3 , water reducing agent 0.024kg / m 3 ;

[0080] The 7d compressive strength of the comparative example is 28.6MPa, and the 28d compressive strength is 38.9MPa; after 250 freeze-thaw cycles, the mass loss rate is 1.5%, and the dynamic elastic modulus decreases to 90.7%. Fig.13 (a) is a surface photograph of the concrete of the comparative example before freeze-thaw cycle. Fig.13 (b) is a surface photo of the comparative concrete after freeze-thaw cycles. After freeze-thaw cycles, the surface peeled off more and some stones were exposed. The magnetic field strength of the concrete was 10.6nT, and the magnetic field strength after magnetization with a 5mT magnetic field was 37.1nT.

[0081] In the above-mentioned embodiment 1, the 7d compressive strength is 33.6MPa, and the 28d compressive strength is 43.7MPa; after 250 freeze-thaw cycles, the mass loss rate is 0.4%, and the dynamic elastic modulus decreases to 96.1%. Figure 13-14 As shown, Fig.14 (a) is a surface photograph of the concrete before freeze-thaw cycle of Example 1, Fig.14 (b) is a surface photograph of the concrete of Example 1 after freeze-thaw cycles. It can be seen that after 250 freeze-thaw cycles, the surface quality of the concrete of Example 1 only shows roughness or a small amount of peeling.

[0082] The low-magnetism and low-hydration heat concrete of the present invention solves the problem of unstable magnetic properties of traditional mineral powder and fly ash, effectively reduces the magnetism and hydration heat of concrete, reduces the risk of concrete cracking, can meet the requirements of relevant special projects, and fills the gap in the low-magnetism mass concrete industry.

[0083] The coarse aggregate uses three-grade crushed stone with a maximum particle size of 80mm, which meets the maximum value allowed by the water transport engineering specifications. At the same time, it can effectively reduce the amount of cementitious materials used, which can be reduced by about 15% compared with ordinary C30 concrete; the reduction of cementitious materials can not only reduce the cost of concrete and bring significant economic benefits, but also reduce the hydration heat in large-volume concrete, and there is no need to add hydration heat inhibitors to reduce the risk of concrete cracking; slag powder accounts for 30% to 40% of the concrete cementitious materials, which can further reduce the amount of cement, reduce the cost of concrete, and reduce hydration heat;

[0084] When preparing concrete, the raw materials are tested by metal detectors to avoid magnetic substances being mixed into the raw materials;

[0085] The slump of the concrete prepared by this scheme is 30mm to 80mm, and the concrete can be transported by hanging tanks, belt conveyors, dump trucks, etc., which is convenient for construction.

[0086] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.

Claims

1. A low magnetic and low hydration heat concrete, characterized in that: The raw material components are as follows: Cementitious material 280-300kg / m 3 , fine aggregate 690-730kg / m 3 , coarse aggregate 1230-1290kg / m 3 , water 134-140kg / m 3 , water reducing agent 2.8-3.0kg / m 3 ; The cementitious material includes cement and slag powder, wherein the cement accounts for 60%-70% and the slag powder accounts for 30%-40%; The magnetic field strength of the cement is less than 5nT, and the magnetic field strength after magnetization by 5mT magnetic field is less than 10nT; The 7d activity index of the slag powder is ≥80%, the 28d activity index is ≥100%, and the loss on ignition is ≤1%; the magnetic field strength of the slag powder is <5nT, and the magnetic field strength after magnetization by a 5mT magnetic field is <10nT; The magnetic field strength of the fine aggregate is less than 5nT, and the magnetic field strength after magnetization by a 5mT magnetic field is less than 10nT; The magnetic field strength of the coarse aggregate is less than 5nT, and the magnetic field strength after magnetization by a 5mT magnetic field is less than 10nT; The magnetic field strength of the concrete is less than 10nT, and the magnetic field strength after magnetization by a 5mT magnetic field is less than 15nT.

2. The low magnetic and low hydration heat concrete according to claim 1, characterized in that: The slag powder is blast furnace physical and chemical slag powder.

3. The low magnetic and low hydration heat concrete according to claim 2, characterized in that: The fine aggregate is machine-made sand, the matrix of the machine-made sand is limestone, and the stone powder content is ≤5%.

4. The low magnetic and low hydration heat concrete according to claim 3, characterized in that: The coarse aggregate is limestone crushed stone, which is three-graded, with particle size of 5-20 mm as the first-grade crushed stone, particle size of 20-40 mm as the second-grade crushed stone, and particle size of 40-80 mm as the third-grade crushed stone. The usage ratio of the first-grade crushed stone, the second-grade crushed stone, and the third-grade crushed stone is 2:5:

3. The large-size third-grade crushed stone can effectively reduce the usage of cementitious materials.

5. The low magnetic and low hydration heat concrete according to claim 1, characterized in that: When antifreeze is required, an air-entraining water-reducing agent is used, and the water reduction rate of the air-entraining water-reducing agent is greater than 25%, so that the air content of the concrete is greater than 3%.

6. The low magnetic and low hydration heat concrete according to claim 3, characterized in that: The cement is ordinary No. 42.5 cement, wherein the components of clinker and gypsum are ≥86%, and the particle size of the cement is concentrated at 40±5 μm.

7. The method for preparing low-magnetic and low-hydration heat concrete according to any one of claims 1 to 6, characterized in that: The steps include: Demagnetization of raw materials: Demagnetize cement, slag powder and fine aggregate separately to meet the magnetic field strength requirements and then set aside; Mixing: Coarse aggregate, demagnetized fine aggregate, demagnetized slag powder and cement are sequentially passed through a belt conveyor equipped with a metal detector. When the metal detector sounds an alarm, the belt conveyor stops and removes the materials within the detection range of the metal detector. Then the belt conveyor sends the remaining materials detected by the metal detector into the mixer according to the proportion. Stirring: The mixed materials are stirred for 15-30 seconds, and then water and a water reducing agent are added and stirred for 2-4 minutes to obtain the concrete.

8. The method for preparing low-magnetic and low-hydration heat concrete according to claim 7, characterized in that: The cement and slag powder are screened using dry magnetic separation equipment to separate magnetic particles from non-magnetic cement and slag powder particles. The magnetic particles are adsorbed in the magnetic field environment and guided to the separation device, while the non-magnetic slag powder particles continue to move along the conveying route for standby use. The fine aggregate is treated by water washing so that the magnetic field strength of the fine aggregate meets the requirements.

9. The method for preparing low-magnetic and low-hydration heat concrete according to claim 7, characterized in that: The concrete has a slump of 30 mm to 80 mm and is transported by a hanging tank, a belt conveyor, or a dump truck.

10. The method for preparing low-magnetic and low-hydration heat concrete according to claim 7, characterized in that: During the mixing process, the cylinder wall and blades of the mixer are both made of 316L stainless steel.

Citation Information

Patent Citations

  • High-performance hydraulic structure concrete and method for producing the same

    CN101172828A

  • Four-graded roller compacted concrete suitable for water power hydraulic engineering and preparation method thereof

    CN104402352A

  • Low-magnetism concrete

    CN106630804A

  • Three-graded broken stone low-heat cement concrete for harbor engineering

    CN111233400A

  • Green high-performance roller compacted concrete and application thereof in extra-high arch dam

    CN114671657A

Cited By

  • Low magnetic concrete and method for producing the same

    CN122667870A